Prevalence and determinants of medications non-adherence among patients with uncontrolled hypertension in primary care setting in Sarawak, Malaysia: a cross-sectional study - Thew, Hui Zhu; Ching, Siew Mooi; Lim, Hooi Min; Anak Mos, Mike Hitler; Tze, Lorna Chin Kin; Low, Kui Feng; Shaari, Nurdarlina; Lin, Jody Yii Sze; Lee, Kai Wei; Ramachandran, Vasudevan (Academy of Family Physicians of Malaysia, 2022)
Introduction: Non-adherence to antihypertensive medications is a leading cause of uncontrolled hypertension and its complications. However, data on the factors associated with non-adherence to antihypertensive medications in the communities of Sarawak, Malaysia, are limited. This study aimed to examine the prevalence and determinants of medication non-adherence among patients with uncontrolled hypertension. Methods: A cross-sectional study was conducted using the systematic sampling method in four government primary healthcare clinics in Sarawak. A self-administered questionnaire was used to obtain socio-demographic data and evaluate non-adherence. Blood pressure was measured, and relevant clinical variables were collected from medical records. Multivariate logistic regression was used to determine the determinants of medication non-adherence. Results: A total of 488 patients with uncontrolled hypertension were enrolled in this study. The prevalence of medication non-adherence was 39.3%. There were four predictors of medication non-adherence among the patients with uncontrolled hypertension: tertiary educational level (odds ratio [OR]=4.21, 95% confidence interval [CI]=1.67–10.61, P=0.010), complementary alternative medication (OR=2.03, 95% CI=1.12–3.69, P=0.020), non-usage of calcium channel blockers (OR=1.57, 95% CI=1.02–2.41, P=0.039) and 1 mmHg increase in the systolic blood pressure (OR=1.03, 95% CI=1.00–1.05, P=0.006). Conclusion: Because of the high prevalence of medication non-adherence among patients with uncontrolled hypertension, primary care physicians should be more vigilant in identifying those at risk of being non-adherent. Early intervention should be conducted to address non-adherence for blood pressure control.